Characterization of bacterial amylolytic activities during cassava solid state fermentation - Flórez, C.; Chuzel, Gérard; Mayer, Jorge Edgard (International Center for Tropical Agriculture, 1993)
Cassava sour starch is a naturally fermented product, which is used in the elaboration of several traditional, flour-based products, like pandeyuca and rosquillas, specially in Colombia and Brazil. Fermentation and drying under the sun confer to the product its specific baking properties (panification power, flavor and aroma). The main problem encountered in the production process, is the fluctuation in product quality. We have set out to study this very interesting solid state fermentation, whose only substrate is cassava starch. The fermentation process takes mainly place under anaerobic and low pH conditions. The production of lactic acid correlates well with the quality of the product. We are presently studying the enzymatic activities of the lactic amylolytic flora (LAB), homo-and heterofermentative. Several LAB strains were isolated on selective MRS starch medium with aniline blue. After Gram, catalase, sugar metabolism (API), and mobility analysis, the best 12 growing bacterial strains were selected for further analysis. They all seem to belong to the genus Lactobacillus. Amylolytic activities of these selected strains were chromatographically enriched from the medium, and their enzymatic parameters (Km. Vmax) determined, as well as their pH and temperature optima. The 12 strains show varying degrees of amylolytic activities. this has been clearly demonstrated on activity polyacrylamide gels, on which the different levels of activity as well as the isozyme patterns were observed. Protein fingerprinting using SDS PAGE was performed on these strains, again demonstrating the non-identity of the strains. Judging by the amylolytic activities and cell count numbers during the fermentation process, it seems likely that Lactobacillus spp are the dominating genus throughout the process.